Manajemen Sumber Daya Keluarga: Pelatihan Perencanaan Keuangan Dan Pembagian Peran Produktif Bagi Ibu Rumah Tangga Di Desa Sindangmukti - Ridwan Hakiki; Endang Syarif (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service activity aims to enhance economic resilience and the quality of family life in Sindangmukti Village through the implementation of character-based Human Resource Management (HRM). The primary challenges faced by the partners include low financial literacy, dependency on informal loans (local predatory lending or "bank emok"), and imbalances in domestic role distribution. The implementation method consisted of four stages: preparation (surveys and module development), socialization (financial planning and role management workshops), mentoring (home visits and digital groups), and evaluation. The results indicated an 85% increase in participants' understanding of daily cash recording and budget allocation. Furthermore, there was a paradigm shift toward more collaborative domestic work distribution and increased integrity in family financial transparency. The availability of the "Family Management Handbook" and intensive mentoring proved to be key factors for program sustainability. It is concluded that adapting HRM principles into the family unit can create a self-reliant, harmonious, and resilient household ecosystem against economic dynamics.